Perception of workers, employers and the legal body on the participation of persons with disabilities in the labor market (Research, Society and Development, 2020)
This study aims to understand the inclusion of people with disabilities in the labor market, based on the perception of workers with and without disabilities and of managers, especially of work posts, and also sought to understand the actions of public legal bodies involved in the process of inclusion of workers with disabilities. It has quantitative and qualitative character, and the data were analyzed descriptively and by triangulation. It was verified the prevalence of males among workers with and without disabilities, and females among managers; the majority of workers in both groups have complete high school, while most managers had an undergraduate degree (Education) and did not participate, during their training, in discussions on the inclusion of people with disabilities in the labor market. The majority of workers with and without disabilities occupied functions in administrative sectors, while most managers worked in educational institutions. From the 192 workers without disabilities, 22.3% worked in the same sector with workers with disabilities. Architectural, attitudinal and communication barriers were identified in the inclusion process. The legal sector addresses the fiscalization. It is possible to verify a masculine predominance between the workers, and feminine among the managers. The schooling level of workers is high school, while for managers is undergraduate degree. All interviewees identified barriers, especially the communication, that directly interfered in the participation of workers with disabilities.